Technology of local microwave heating - Бондаренко, И.Н.; Бендеберя, Г.Н.; Галат, А.Б.; Горбенко, Е.А. (Radiotekhnika, 2019)
Experimental studies of the possibilities of local microwave heating technology practical implementation were carried out. The correspondence of the existing theoretical models of the process to what is happening in practice is shown. The results of measuring the temperature distribution over the sample when exposed to a radiating microwave coaxial probe are given. The directions for further improvement of the operating modes and the main components of the microwave modifier are determined.